Differences in trunk range of motion for various flexibility protocol types, particularly in quarterbacks wearing rib protectors - Walker, M. A.; Li, Y.; Samson, C. O.; Simpson, K. J.; Foutz, T.; Brwon, C. N. (Sport-Orthopädie - Sport-Traumatologie, 2021)
Background: It is unclear how rib protectors may affect trunk mobility in American football players. The purposes of the study were: 1) to determine which flexibility protocol (active-assisted, maximal-speed, self-selected) exhibits the highest range of motion for trunk lateral flexion and axial rotation and 2) to determine the effect of rib protectors (hard-rib and soft-rib protectors and control: compression shirt only) on trunk range of motion. Methods: Eleven male participants with competitive quarterback experience were recruited. Participants were instructed to rotate the trunk in the lateral flexion and axial rotation directions during each flexibility protocol and rib protector condition. The lower-thoracic range of motion were measured. Results: Two-way repeated measures ANOVA (flexibility protocol by rib protector) demonstrated significant main effect of flexibility protocol for lateral flexion, but not axial rotation. The range of motion during self-selected protocol was significantly greater than maximal-speed protocol by approximately 7° (p = .009). Conclusions: Self-selected and maximal-speed protocol produced the highest lateral flexion and axial rotation range of motion, respectively, and can be used to test the influence of rib protectors and potentially other sports equipment on thoraco-lumbar range of motion. Additionally, rib protectors likely do not affect trunk range of motion needed to throw long-distance passes or other movements as performed by football quarterbacks.